Research Potential of Traditional Buildings from an Ethnographic and Ethnoscience Perspective Through SLR (Systematic Literature Review) in SDGs Studies 2015-2025 - Rahmatta Thoriq Lintangesukmanjaya; Oktamia Ramadhani; Hanandita Veda Saphira (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The preparation of a systematic literature review that specifically discusses the ethnoscience perspective is examined in the form of bibliometric analysis findings in the relationship between SDGs and culturalization of culture in the realm of science. Method: Quantitative descriptive research, through bibliometric analysis studies using data from the Scopus database to map trends and focus on SDGs research with culture and ethnophysics in traditional buildings through international literature. A total of 462 documents were analyzed using the PRISMA design to identify research trends and conduct a literature synthesis. Results: Based on publication trend data in the Scopus database for the period 2021–2026, it can be seen that research on traditional buildings from the perspective of sustainable design development studied through ethnographic approaches and ethnoscience values ​​shows an increasing trend. Traditional building architecture has long been seen as a manifestation of the reciprocal relationship among humans, natural conditions, and cultural values passed down from generation to generation. Novelty: Traditional buildings have great potential for study through an ethnographic approach because they reflect cultural values, local knowledge, and the living practices of developing communities. This study contributes to the preservation of cultural heritage and the development of sustainable settlement concepts. This is in accordance with the SDG study point 11 concerning sustainable cities and communities.